THEORETICAL FOUNDATIONS OF STUDYING THE FORMATION OF CHARACTER TRAITS IN SCHOOLCHILDREN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article includes questions about the correct use of human psychological capabilities and their implementation, and on the basis of this, assign plans for the future. This is considered the main task of every state and every nation. Each person must realize that they are part of the community and the people.